2013
DOI: 10.1136/bjsports-2013-092404
|View full text |Cite
|
Sign up to set email alerts
|

Barefoot running: an evaluation of current hypothesis, future research and clinical applications

Abstract: Barefoot running has become a popular research topic, driven by the increasing prescription of barefoot running as a means of reducing injury risk. Proponents of barefoot running cite evolutionary theories that longdistance running ability was crucial for human survival, and proof of the benefits of natural running. Subsequently, runners have been advised to run barefoot as a treatment mode for injuries, strength and conditioning. The body of literature examining the mechanical, structural, clinical and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 68 publications
2
52
0
1
Order By: Relevance
“…8). These results are consistent with previous studies that have reported that RFS unshod running of habitually shod runners have higher VALR (Paquette et al, 2013); more specifically, the medial forefoot (first and second metatarsal) bears more loading compared with other conditions, which is linked with calluses observed in plantar skin (Grouios, 2004), forefoot pain (Keijsers, Stolwijk, Louwerens, & Duysens, 2013) or even metatarsal stress fracture (Nagel, Fernholz, Kibele, & Rosenbaum, 2008;Tam et al, 2014). Further, the RFS unshod running of habitually shod runners and FFS unshod running of habitually unshod runners show greater pressure time integral than RFS and FFS shod running.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…8). These results are consistent with previous studies that have reported that RFS unshod running of habitually shod runners have higher VALR (Paquette et al, 2013); more specifically, the medial forefoot (first and second metatarsal) bears more loading compared with other conditions, which is linked with calluses observed in plantar skin (Grouios, 2004), forefoot pain (Keijsers, Stolwijk, Louwerens, & Duysens, 2013) or even metatarsal stress fracture (Nagel, Fernholz, Kibele, & Rosenbaum, 2008;Tam et al, 2014). Further, the RFS unshod running of habitually shod runners and FFS unshod running of habitually unshod runners show greater pressure time integral than RFS and FFS shod running.…”
Section: Discussionsupporting
confidence: 94%
“…The different FFS styles between shod and unshod running of habitually unshod runners is plausible when considering the proprioceptive ability of humans, which is believed to adjust body function according to running surface or environment (Gu, Lu, Mei, Li, & Ren, 2014;Lieberman, 2012;Sousa & Tavares, 2013;Sousa et al, 2012;Tam et al, 2014). RFS shod running of habitually shod runners has larger passive impact peak and active impact peak compared with RFS unshod running (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Proposed benefits include injury prevention, enhanced proprioception, foot muscle strength and running economy, as well as superior running biomechanics 1. The few reports of long-term barefoot locomotion investigated mainly adult populations.…”
Section: Why Did I Do It?mentioning
confidence: 99%